Communication as a cultural performance Islamic employees’ meaning of organizational culture at Catholic institutions - Nugraheni, Yuli; Subiakto, Henri; Isnaini, Santi (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research focuses on the organisational culture of a university with a religious identity, namely Widya Mandala Surabaya Catholic University (WMSCU). Pacanowsky and Trujillo suggest that this identity generates a unique organizational culture. This research highlights the experiences of organisational members who have belief values that are different from their organisational values. This study aims to describe the experiences and meanings of Muslim employees regarding Patron Day commemoration as a form of organisational culture at WMSCU. A qualitative approach and phenomenological method are employed in this research. The findings indicate that Muslim employees interpret the Patron Day commemoration as a beneficial activity, recognizing and emulating the values of Patron John Paul's life as a learning opportunity of noble values. It serves as a platform for learning beyond their own beliefs. Ultimately, this meaning contributes to the emergence of religious tolerance, which is reflected in the organisational communication patterns among its members, particularly in personal relationships. The study underscores the importance of striving for two-way communication in the form of interpersonal dialogue to foster a positive organisational culture.